Keap1–Nrf2 regulated redox signaling in utero: Priming of disease susceptibility in offspring - Chapple, Sarah J.; Puszyk, William M.; Mann, Giovanni E. (Free radical biology & medicine, 2015)
Intrauterine exposure to gestational diabetes, pre-eclampsia or intrauterine growth restriction alters the redox status of the developing fetus. Such pregnancy-related diseases in most cases do not have a readily identifiable genetic cause, and epigenetic 'priming' mechanisms in utero may predispose both mother and child to later-life onset of cardiovascular and metabolic diseases. The concept of ‘fetal programing’ or ‘developmental priming’ and its association with an increased risk of disease in childhood or adulthood has been reviewed extensively. This review focuses on adaptive changes in the in utero redox environment during normal pregnancy and the consequences of alterations in redox control associated with pregnancies characterized by oxidative stress. We evaluate the evidence that the Keap1–Nrf2 pathway is important for protecting the fetus against adverse conditions in utero and may itself be subject to epigenetic priming, potentially contributing to an increased risk of vascular disease and insulin resistance in later life. •Intrauterine exposure to oxidative stress alters the redox status of the developing fetus.•In utero developmental priming under oxidative stress increases the risk of disease in offspring.•Nrf2 affords protection against oxidative stress in a diabetic environment.•Gestational diabetes is associated with impaired Nrf2 redox signaling in fetal vascular cells.•Nrf2 activation may provide a therapeutic target to counteract oxidative stress in adverse pregnancies.